2017
DOI: 10.1071/ah16233
|View full text |Cite
|
Sign up to set email alerts
|

Going digital: a narrative overview of the clinical and organisational impacts of eHealth technologies in hospital practice

Abstract: Objective. The aim of the present study was to determine the effects of hospital-based eHealth technologies on quality, safety and efficiency of care and clinical outcomes.Methods. Systematic reviews and reviews of systematic reviews of eHealth technologies published in PubMed/ Medline/Cochrane Library between January 2010 and October 2015 were evaluated. Reviews of implementation issues, nonhospital settings or remote care or patient-focused technologies were excluded from analysis. Methodological quality was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 18 publications
2
80
2
3
Order By: Relevance
“…Integration of the procedure into hospital EHR systems could also help routinize use of this program, and consistent use of the program could increase comfort and ease of use. Systematic reviews of the utilization of health information technology such as EHRs found that their use can increase adherence to protocolbased care, and may improve efficiency and level of patient care (Chaudhry et al, 2006;Keasberry, Scott, Sullivan, Staib, & Ashby, 2017). Computerized decision support systems, which integrate patient information and provide support for provider decision making, could be programmed to provide alerts or prompts when a call to the MROT would be recommended, though empirical evidence supporting the impact of these systems on quality of care is somewhat weak (Black et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Integration of the procedure into hospital EHR systems could also help routinize use of this program, and consistent use of the program could increase comfort and ease of use. Systematic reviews of the utilization of health information technology such as EHRs found that their use can increase adherence to protocolbased care, and may improve efficiency and level of patient care (Chaudhry et al, 2006;Keasberry, Scott, Sullivan, Staib, & Ashby, 2017). Computerized decision support systems, which integrate patient information and provide support for provider decision making, could be programmed to provide alerts or prompts when a call to the MROT would be recommended, though empirical evidence supporting the impact of these systems on quality of care is somewhat weak (Black et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Keasberry et al 6 provided a narrative review of systematic reviews of the effects of EMR, CPOE, CDSS and ePrescribing published between 1 January 2010 and 31 October 2015. We update this review by replicating their search methods to review studies published from 1 November 2015 to 1 August 2017.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this paper is to provide an assessment of the current literature on the effects to be expected from hospital implementations of eHealth technologies. 6 This paper provides the detailed background evidence for our recently published Deeble Institute Evidence Brief. 7…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on previous research on Digital Hospitals [15] indicates that eHealth technologies improve the efficiency and appropriateness of care and safety, while the effects on mortality, readmissions, total costs as well as patient and provider experience still remain uncertain.…”
Section: Discussionmentioning
confidence: 99%